An Analysis of the Section on Causality in Khojazāda’s Tahāfut - Muhammet Fatih Kılıç (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
In this article, the nineteenth section of Khojazāda’s (d. 893/1488) Tahāfut, which was devoted to the problem of causality in an example of the works under the same title written during the fifteenth century and composed with the patronage of the Ottoman sultan Mehmed II (d. 886/1481), is subjected to a critical analysis. His discussion follows a critical course with respect to al-Ghazālī (d. 505/1111) in context. This could be detected most clearly in his vindication of Avicenna (d. 428/1037) against al-Ghazālī’s accusation of the philosophers’ denial of miracles. Moreover, Khojazāda’s discussion has certain differences with al-Ghazālī’s at both the conceptual and the argumentative levels. The most striking differences at the argumentative level is Khojazāda’s grounding of his own conception of revelation and miracles on Avicennia’s, rather than al-Ghazālī’s, theory of prophethood. By the same token, he offered a practical response to the imputation that the Avicennian system leaves no room for the possibility of miracles. At the conceptual level, furthermore, he distinguished between complete and incomplete causes, in contradistinction with al-Ghazālī, and thereby opened another ground in order to demonstrate the inability of those natures that he viewed as incomplete causes to produce their own effects. On the other hand, Khojazāda concurs with al-Ghazālī that causality did not presume an ontological necessity, yet this condition did not incur defects on the certainty of our knowledge.